Speech Therapy of Visually Impaired People as a Sub-discipline of Detailed Speech Therapy and Part of its Modern Structural Concept - Zaorska, Marzenna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2016)
The lack or a serious impairment of sight, especially if present from the moment of birth or early childhood can, but not necessarily, handicap, limit and sometimes even disable a person’s activities in life. It can complicate physical, mental and social development and demands a purposed use of other senses in the process of cognition of the surrounding reality and gaining essential information. Sight disability shows its specificity also in the area of obtaining speech skills, using words and non-verbal components of communication during interpersonal relations. What results from those reasons is the need to include people with a certain type of disability, that have difficulties with speaking, in a program of special speech therapy aid aimed at removal or minimizing the unveiled problems. The article highlights chosen disabilities in the area of communicational functioning of people with sight disability and signalizes certain nuance of therapeutic actions.